Sleep quality and psychobiological aspects of Brazilian Paralympic athletes in the London 2012 pre-Paralympics period - Dayane Ferreira Rodrigues; Andressa Silva; João Paulo Pereira Rosa; Francieli Silva Ruiz; Amaury Wagner Veríssimo; Ciro Winckler; Edilson Alves da Rocha; Andrew Parsons; Sergio Tufik; Marco Tulio de Mello (Universidade Estadual Paulista (UNESP), 2015)
The objective of the study was to evaluate the psychobiological aspects of the Paralympic athletes athletics mode, before the London Paralympic Games 2012. We evaluated 40 athletes without 31 men and 9 women who were selected by the Brazilian Paralympic Committee to be part of the Brazilian delegation. For the evaluation of psychobiological aspects used questionnaires: Trait Anxiety Inventory-State, POMS, the Beck Depression questionnaire Pittsburgh Epworth Scale to assess, respectively, anxiety, mood, depression, sleep and sleepiness. For trait anxiety and state anxiety, athletes exhibited a mean level of anxiety in relation to the profile of mood states and higher intensity values than any other dimensions. The lower total sleep time was in athletes with bad sleep, sleep deficiency was lower in athletes with poor sleep and total sleep time was lower for those who had efficiency < 85%. All psychobiological variables evaluated in pre-competition period were normal for the athletes of the Brazilian Paralympic athletics team that took part in the London 2012 Paralympic Games.